2017
DOI: 10.1039/c7cp02465g
|View full text |Cite
|
Sign up to set email alerts
|

Stability and growth mechanism of self-assembling putative antifreeze cyclic peptides

Abstract: Cyclic peptides (CPs) that self-assemble in nanotubes can be candidates for use as antifreeze proteins. Based on the cyclic peptide sequence cyclo-[(l-LYS-d-ALA-l-LEU-d-ALA)], which can stack into nanotubes, we propose a putative antifreeze cyclic peptide (AFCP) sequence, cyclo-[(l-LYS-d-ALA)-(l-THR-d-ALA)], containing THR-ALA-THR ice binding motifs. Using molecular dynamics simulations we investigate the stability of these cyclic peptides and their growth mechanism. Both nanotube sequences get more stable as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…TPS has been used, for instance, to study dissociation pathways of tube-forming cyclic peptides with the all-atom AMBER force field. 155 The study revealed multiple possible dissociation pathways ( Fig. 7 ).…”
Section: Molecular Simulation Techniquesmentioning
confidence: 98%
“…TPS has been used, for instance, to study dissociation pathways of tube-forming cyclic peptides with the all-atom AMBER force field. 155 The study revealed multiple possible dissociation pathways ( Fig. 7 ).…”
Section: Molecular Simulation Techniquesmentioning
confidence: 98%
“…The group of Balasubramanian studied the polymerization process of BTAbased supramolecular polymers in nonane at AA and CG level [45,72]. The group of Bolhuis recently used transition path sampling to monitor the stability and growth mechanism of cyclic peptide nanotubes in water at atomistic level [79]. Explicit-water CG models (see above) for BTA monomers also allowed to follow supramolecular polymerization in time, monitoring the growth of the aggregates and the amplification of order (core-core coordination, see Figure 4) inside them during the cooperative polymerization process [29].…”
Section: Supramolecular Polymerizationmentioning
confidence: 99%
“…In the last years, enhanced sampling computational techniques have been proven very effective to tackle this issue [81][82][83][84][85][86]. For example, Botzakis et al recently used transition path sampling simulations to identify the pathway of incorporation (polymerization) in tubules of peptide macrocycles [79]. Particularly interesting, infrequent well-tempered metadynamics (WT-MetaD) [81] simulations were recently proven an efficient tool to explore rare exchange events, providing information on the pathway, rate limiting steps and their relative kinetics in once [82].…”
Section: Supramolecular Dynamics At Submolecular Resolutionmentioning
confidence: 99%
“…Note that these kind of TPS applications have only become possible with the development of the spring shooting algorithm. [ 67 ]…”
Section: Applicationsmentioning
confidence: 99%